Edukasi Peningkatan Nilai Jual Produk dan Bisnis Teh Celup Cascara di Kampung Cikoneng Babakan, Desa Cibiru Wetan - Asri Widyasanti; Muhammad Luthfi Mukhlisin; Hilmi Lisan Shidqi; Saniyya Rhomadina Purwanto; Sheila Rizky Nur Hermawan; Shintya Devita Maharani; Zahra Dwiandra Arbuana (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
This community service activity has the theme "Education on Increasing the Selling Value of Products and Cascara Tea Bag Business in Cikoneng Babakan Village, Cibiru Wetan Village". The purpose of this activity was to increase the selling value of the cascara tea business, which of course will increase sales by providing education to cascara tea business owners. The implementation of this activity uses a descriptive method with survey and interview techniques. Cascara tea business education activities are carried out by visiting residents' homes. The results achieved were that the residents of Cikoneng Babakan Village, Cibiru Wetan Village had received education about making cascara tea by fermentation, the bioactive content contained in cascara tea, optimal storage to maintain the quality of cascara tea, how to pack cascara tea, and how to calculate the Basic Price Production (HPP) of TangSer brand cascara tea. Handbooks were also given so that residents had standard procedures for handling cascara from upstream to downstream.